2017
DOI: 10.1007/s10555-017-9699-4
|View full text |Cite
|
Sign up to set email alerts
|

(Immuno)proteasomes as therapeutic target in acute leukemia

Abstract: The clinical efficacy of proteasome inhibitors in the treatment of multiple myeloma has encouraged application of proteasome inhibitor containing therapeutic interventions in (pediatric) acute leukemia. Here, we summarize the positioning of bortezomib, as first-generation proteasome inhibitor, and second-generation proteasome inhibitors in leukemia treatment from a preclinical and clinical perspective. Potential markers for proteasome inhibitor sensitivity and/or resistance emerging from leukemia cell line mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 155 publications
(169 reference statements)
0
33
0
Order By: Relevance
“…If proteasome inhibitor therapies impair bone growth and density, this would have significant implications for the administration of these drugs to children in order to treat any condition, not just osteosarcoma. Around a dozen clinical trials have been conducted, and more are underway, evaluating proteasome inhibitors for a number of pediatric cancers, mostly leukemias, 86 as well as for suppressing transplant rejection. 87 None of these studies have unveiled any effect of proteasome inhibitors on participants' bones, but emergence of such late effects would not be expected given the short-term nature of these trials (and the poor survival of many participants).…”
Section: Discussionmentioning
confidence: 99%
“…If proteasome inhibitor therapies impair bone growth and density, this would have significant implications for the administration of these drugs to children in order to treat any condition, not just osteosarcoma. Around a dozen clinical trials have been conducted, and more are underway, evaluating proteasome inhibitors for a number of pediatric cancers, mostly leukemias, 86 as well as for suppressing transplant rejection. 87 None of these studies have unveiled any effect of proteasome inhibitors on participants' bones, but emergence of such late effects would not be expected given the short-term nature of these trials (and the poor survival of many participants).…”
Section: Discussionmentioning
confidence: 99%
“…The proteomic data suggested that that the level of the relatively low abundant proteasome subunit beta type-8 (PSMB8) (β5i) was decreased in ibuprofen treated male mice (Supplemental Table 1). During stress conditions, the constitutive proteasome β1, β2 and β5 subunits of 20 S proteasome are replaced by β1i, β2i, and β5i immunoproteasome counterparts [24][25][26] . Western blotting data showed that the expression levels of β5i immunoproteasome subunit was significantly decreased in ibuprofen treated male livers, consistent with the proteomic data ( Fig.…”
Section: Proteasome Dysfunctionmentioning
confidence: 99%
“…15 In addition, responses to PI in other hematological malignancies have been contradictory. 6,16,17 Similarly, promising preclinical data obtained with PI in models of solid tumors have not been confirmed in the clinic, 15 probably as a consequence of impaired drug distribution, requiring higher dosages, not applicable for the toxic effects. Therefore, the design of a new generation of ubiquitinproteasome pathway inhibitors and the identification of novel combination strategies is essential to overcome resistance and broaden the applicability of this class of drugs to other hematological malignancies, and possibly to solid tumors.…”
Section: Introductionmentioning
confidence: 99%